Association between chronic conditions, multimorbidity, and dependence levels in Chinese community-dwelling older adults with functional dependence: a cross-sectional study in south-central China - Hu, Heng-Yu; Hu, Ming-Yue; Feng, Hui; Cui, Pan-Pan (Frontiers in Public Health, 2024)
Background The rising prevalence of multimorbidity and functional dependence in community-dwelling older adults contribute to the demand for home care services. Evidence on how chronic conditions, especially multimorbidity, affect dependence levels among older adults with functional dependence in a socio-cultural context is much needed to inform policy, workforce, aged care service development to meet the care needs of this population. Objectives This study aimed to determine the association between chronic conditions, multimorbidity and dependence levels among Chinese community-dwelling older adults with functional dependence. Methods A cross-sectional study was conducted with 1,235 community-dwelling older adults with functional dependence in Hunan province, China, from June to October 2018. Data on socio-demographic factors, cognitive function, vision and hearing conditions, activities of daily living (ADLs), and health conditions were collected, and binary logistic regression analyses were used to determine the association between chronic conditions, multimorbidity and dependence levels, with adjustments for relevant covariates. Results Among the participants, 62.9% had multimorbidity. Parkinson’s disease, stroke, COPD, hypertension, mood and psychotic disorders (Anx/Sch/Dep) were significantly associated with high levels of functional dependence. After adjusting for demographic variables, cognitive function, vision, and hearing conditions, we observed a significant relationship between multimorbidity and higher functional dependence, but this association became insignificant when including certain chronic diseases closely associated with high-level dependence. Study revealed that Parkinson’s disease and stroke notably increase dependency risk across seven ADL domains, demonstrating their extensive impact on daily functioning. Conclusion The prevalence of multimorbidity among Chinese community-dwelling older adults with functional dependence is very high. The association of multimorbidity with functional dependence is mediated by specific chronic conditions. These findings highlight the necessity of adopting an integrated care model that combines medical and social care, with a particular emphasis on managing multimorbidity and critical chronic conditions that lead to severe functional dependence to preventing and diminish the onset of disabilities.